Intercalation of ZnO with 2-mercapto – N` - (2-mercaptoacetyl) and Study of its controlled released. - Jabir Yasser, Muhannad (Al-Qadisiyah Journal of Pure Science, 2018)
Metal nanoparticles have been extensively studied over the last decade. Nanomaterials were an important subject in basic and applied sciences. Nanoparticles of zinc oxide compounds have received considerable attention because of their unique antibacterial, antifungal, properties. The aim of this work is to prepare a hybrid Nano-crystalline composite of zinc oxide molecules using the chemical method and the diagnosis of ZnO-NPs using FT-IR, AFM and XRD, the intercalation of 2- (2-mercaptoacetyl) with ZnO accurse by the ion exchange method. The shape of the fibrous particles was determined by the atomic force microscope. The dimensions of these compounds ranged from 24.6*30.8 nm and Mean grain size (57.1) nm . The release ratio of the atoms of this compound (pH = 4,6,8,13), . The reaction is governed by the pseudo second order reactions.